Lean Manufacturing applied to Brazilian road transportation: bibliometric analysis using Proknow-C - Garcia, Daniel Carlos Martins; Detino, Junior Soares; Silva Junior, Orlando Marques da; Salazar, Franco Sidney Condor; Cosvosk, Enzo Almenara; Servare Junior, Marcos Wagner (Brazilian Journal of Production Engineering, 2024)
The present article explores the use of the Lean Manufacturing methodology in the road transport sector in Brazil, highlighting its relevance since the 1950s with the implementation of Juscelino Kubitschek's "Plano de Metas." Using the ProKnow-C methodology, the study selected and analyzed relevant articles, identifying trends and patterns in the application of Lean Manufacturing in the sector. The Lean Manufacturing methodology focuses on eliminating waste and improving efficiency, being especially advantageous for road transport. The study includes examples of application, such as improving service quality, reducing costs, and optimizing processes through tools like Gantt charts, Excel, and Google Maps. Additionally, it addresses eco-efficiency, promoting sustainable management aligned with Lean Manufacturing principles. The research concludes that the application of Lean Manufacturing in road transport is fundamental to increasing operational efficiency and customer satisfaction. The ProKnow-C methodology was effective in selecting and analyzing the literature, providing a solid foundation for future research and practical applications in the road transport sector.
Keywords: Road transport; Lean manufacturing; Operational efficiency; Toyota Production System